The good fight. Season five [videorecording (DVD)] - Baranski, Christine; Steele, Sarah, 1988-; Nyambi, Nyambi; Boatman, Michael, 1964- (Paramount Home Entertainment, 2022)
Diane is forced to question whether it's appropriate for her to help run an African American law firm with Liz when the firm loses two top lawyers. Meanwhile, Marissa and the firm become entangled with Hal Wackner, a regular Chicagoan who decides to open his courtroom in the back of a copy shop.